Pengaruh Gaya Hidup Dan Ekuitas Merek Terhadap Keputusan Pembelian Sepatu Merek Nike: Survei Pada Mahasiswa Universitas Perjuangan Tasikmalaya - Nadia Nur Qalby; Ari Arisman; Depy Muhamad Pauzy (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims to determine the simultaneous and partial effect of Lifestyle and Brand Equity on the Purchase Decision of Nike Brand Shoes (Survey on Students of the University of Perjuangan, Tasikmalaya). The research method used in this research is to use a descriptive quantitative research method with a survey approach. Respondents in this study were 101 students of the University of Perjuangan Tasikmalaya. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results showed that Lifestyle and Brand Equity simultaneously had a significant effect on Purchasing Decisions. Lifestyle partially has a significant effect on the Purchase Decision. Brand Equity partially has a significant effect on Purchasing Decisions.